Matrix metalloproteinase inhibition causes luminal narrowing and ring thickening in the cricoid cartilage - Martinez-Alvernia, Efrain A; Mankarious, Leila A (Otolaryngology-head and neck surgery, 2010)
Luminal expansion of the cricoid cartilage appears to be stunted by loss of luminal epithelium (LE) and can be enhanced by transforming growth factor-beta3 (TGF-beta3). When both the LE and perichondrium are disrupted, matrix metalloproteinase (MMP) levels within adjacent chondrocytes are diminished but can be restored by exogenous TGF-beta3. Cricoid growth stunting and luminal expansion that occur in the absence and presence of MMP activity, respectively, suggest that MMPs play an important role in normal subglottal development. The study objective was to determine if MMP inhibition affects cricoid expansion and by what mechanism, which will in turn help to define the mechanism of action of TGF-beta3-induced luminal expansion. Ex vivo, in vitro whole organ culture of subglottises grown with and without the presence of an MMP inhibitor. Tertiary care facility. Subglottises from 20 neonatal mice were divided into 10 grown with an MMP inhibitor, GM6001, and 10 grown in basic medium alone. The luminal cross-sectional area, apoptosis levels, cell proliferation rates, and presence or absence of cleaved aggrecan fragments were determined. Subglottises that were exposed to the MMP inhibitor displayed statistically significant luminal narrowing, accompanied by apparent circumferential thickening of the cricoid ring, relatively decreased apoptosis, increased chondrocyte proliferation, and decreased amounts of aggrecan cleavage fragments in the extracellular matrix. Matrix metalloproteinases likely play a significant role in growth of the cricoid cartilage such that their inhibition leads to marked changes in the shape of the ring.